IMPLEMENTASI MODEL PEMBELAJARAN RADEC DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Rindiyani, Adinda Febriele; Diana, Siska Mega; Izzatika, Amrina; Khairani, Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the RADEC learning model in improving the critical thinking skills fifth-grade elementary school students in Indonesian language learning. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research population consisted of all 38 fifth-grade students at SD Negeri 2 Yukum Jaya, who were selected through purposive sampling. Data were collected using pretest and posttest. Data analysis involved simple linear regression and t-tests, which met the prerequisite tests, including normality and homogeneity. The results pf the simple linear regression analysis showed a significance value of 0.002 < 0.05, while the t-test showed a significance value of 0.044 < 0.05. Therefore, it was conclude that the implementation of the RADEC learning model was proven to be effective in improving students' critical thinking skills.